KETERBATASAN APBD DAN DAMPAKNYA TERHADAP KESEJAHTERAAN ASN DAERAH: STUDI KASUS POLEMIK GAJI PPPK - Djasuli, Mohamad; Stevani, Arsita Dwi Ayu; Wulandari, Dila Aprilia; Hayat, Zidan Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limitation of the Regional Revenue and Expenditure Budget (APBD) is one of the crucial issues in this study aims to analyze the impact of the limited Regional Revenue and Expenditure Budget (APBD) on the welfare of the State Civil Apparatus (ASN), especially in the polemic of the salaries of Government Employees with Work Agreements (PPPK). The method used is descriptive qualitative through literature study and public policy analysis based on fiscal decentralization theory. The results of the study show that the imbalance between the central government's ASN appointment policy and regional fiscal capacity causes budget pressure, which has an impact on salary payment delays, uncertainty of benefits, and a decrease in PPPK's work motivation. In addition, weak coordination between levels of government worsens the implementation of the merit system in ASN management. The conclusion of this study emphasizes that the limitations of the APBD have direct implications for the welfare of regional civil servants, so that more synchronous policies and strengthening regional fiscal capacity are needed to ensure the sustainability of the payment of civil servant rights.